A pilot randomized controlled trial comparing noradrenaline and adrenaline as a first-line vasopressor for fluid-refractory septic shock in neonates - Garegrat, Reema; Patnaik, Suprabha; Suryawanshi, Sonali; Chetan, Chinmay; Banait, Nishant; Singh, Pari; Kallimath, Aditya; Soni, Naharmal B.; Singh, Yogen; Suryawanshi, Pradeep (Frontiers in Pediatrics, 2024)
Background and study design: Limited data exists on noradrenaline therapy in neonatal septic shock. We compared the efficacy of noradrenaline with adrenaline in neonatal septic shock. This single center, open label, pilot randomized controlled trial included neonates with clinical evidence of sepsis and shock. Study outcomes: Primary outcomes were: 1) resolution of shock one hour after treatment, and 2) mortality during hospital stay. Secondary outcomes included: need of additional vasopressors; hemodynamic stability without further administration of vasopressors for ≥ 2 hours; changes in blood pressure and heart rate after 1 hour of vasopressor treatment; and morbidities during the hospital stay. Results: Of 65 eligible neonates, 42 were randomized (21 each in adrenaline and noradrenaline treatment arms) between August 2020 and January 2022 , at level III neonatal intensive care unit (NICU) of Bharati Vidyapeeth Deemed University Medical College and Hospital (BVDUMCH). The mean (SD) gestational age and mean (SD)birth weight were 36.1(4.2) weeks and 1.8 (0.2) kilograms birth weight for noradrenaline and 36.9 (4.1) weeks and 1.7 (0.7) kilograms for adrenaline. Shock resolved within 1 hour of vasopressor therapy in 76.2% neonates in the noradrenaline arm and 61.9% in adrenaline arm (p value-0.53). Mortality during hospital stay was 28.6%(6/21) in noradrenaline group and 33.3% (7/21) in adrenaline group (p value-0.58). Additional vasopressors were required in 23.8% neonates of the noradrenaline group compared to 38.1% neonates in adrenaline arm (p value-0.53) . Median (SD) duration of intensive care stay was 6 (SD) days in the noradrenaline group and 10 (SD) days in the adrenaline group (p value-0.045).Among neonates with septic shock, the efficacy of noradrenaline was comparable to adrenaline in resolving septic shock after one hour of infusion and on the mortality during hospital stay. Trial Registration: Clinical Trials Registry -India with identifier CTRI/2020/08/027185 (17/08/2020) Hemodynamically significant patent ductus arteriosus (hsPDA) Acute kidney injury (AKI) Intraventricular hemorrhage (IVH) Periventricular leukomalacia (PVL) Necrotizing enterocolitis (NEC)